A hydrogel/fiber composite scaffold for chondrocyte encapsulation in cartilage tissue regeneration. Issue 86 (1st September 2016) - Mohabatpour, Fatemeh; Karkhaneh, Akbar; Sharifi, Ali Mohammad
Abstract : A composite was constructed by embedding fragmented electrospun PLA nanofibers into an alginate- graft -hyaluronate hydrogel to generate an ECM-mimicking environment for cartilage repair. Abstract : Electrospun fiber–hydrogel composites have been recently utilised to mimic the native extracellular matrix (ECM), in order to overcome the poor mechanical properties of hydrogels as well as restricted cell infiltration of electrospun fibers. In this study, poly(lactic acid) (PLA) fibers were firstly prepared via electrospinning method and then fragmented through aminolysis reaction. Next, hyaluronic acid (HA) was chemically grafted to the alginate (Alg) backbone by esterification reaction. Composite scaffolds were constructed with incorporation of fragmented nanofibers into alginate- graft -hyaluronate (Alg- g -HA) solution in 1 : 1 and 1 : 2 ratios and then gelation occurred by calcium chloride solution (102 mM). Scanning electron microscopy (SEM) images showed the formation of continuous and uniform PLA nanofibers without beads. The diameter and length of fragmented nanofibers were measured which were 0.568 ± 0.254 μm and 7.060 ± 4.963 μm (mean ± SD), respectively. Grafting of HA onto the Alg backbone was confirmed by nuclear magnetic resonance ( 1 H NMR) and Fourier transform infrared (FTIR) spectroscopy. Incorporation of fragmented nanofibers into the alginate–hyaluronic acid hydrogel increased the compressive modulus by around 81% compared to the nanofiber-free hydrogel scaffold control and decreased water uptake. The cytocompatibility of the scaffolds was confirmed by using the MTT assay and acridine orange/propidium iodide (AO/PI) staining. SEM images revealed that chondrocytes maintained their spherical morphology in the composites. Hematoxylin and eosin (H&E) staining illustrated localization of the chondrocytes into lacuna with a round morphology and a uniform distribution within the scaffolds. Alcian blue staining also showed that the chondrocytes could produce a cartilage specific matrix within the composites. Therefore, it could be concluded that PLA nanofiber/Alg–HA hydrogel composites can provide a suitable microenvironment for chondrocytes during cartilage repair.